"Jack of all trades"? Exploring the dual role of the subject teaching guidance counsellor in Irish schools. - Elftorp, Petra; Murphy, Edel (British Journal of Guidance & Counselling, 2026)
Many Irish school guidance counsellors have a "dual role", as their timetable is split between subject teaching and guidance counselling, but their experiences of managing both roles have been underexplored. This article presents the findings of an interpretivist qualitative study which explores experiences of dual role teachers/guidance counsellors, with particular attention to potential role conflicts and the impact of the dual role on relationships with staff and students. The findings from the 26 semi-structured qualitative interviews suggest that it can be challenging to fully master either role when having to combine both. Further, a common dilemma was identified, whereby one has to choose between adequately supporting a student with their pressing problem, or to rush to a classroom for one's timetabled class. Conversely, however, the two roles may also complement each other, specifically in terms of facilitating the development of relationships with students.